Lignans from Daphne feddei Levl. var and Their Cytotoxicity - Wang, Lan; Chen, Zhang-Yu; Jiang, Ci-Qing; Liao, Zhen; Yang, Guangyu; Chzn, Yong-Kuang (Asian Journal of Chemistry, 2010)
A new neolignan, daphnelignan C (1), together with four known one, were isolated from the leaves of Daphne feddei levl. var. The structures of daphnelignan C (1) were elucidated by spectroscopic methods, including extensive 1-D and 2-D NMR techniques. All the five compounds were tested for their cytotoxicity. Compound daphnelignan C (1) showed significant potential cytotoxic ability and weak anti HIV-1 activities.